Mempertahankan Eksistensi Media Cetak Di Tengah Gempuran Media Online - I Made Suyasa; I Nyoman Sedana (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2020)
The development of information and communication technology has brought a large flow of changes to the media industry, especially print media. The proliferation of online media is a threat to conventional media. In this digital age, information and news are more easily obtained from various online sources. This condition has caused a number of print media industries in the country to